Penerapan Model Pembelajaran Air Berbasis Edutaiment terhadap Kemampuan Pemahaman Konsep Matematika - Hidayati, Atika Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the application of the edutaiment-based water learning model at SD Negeri 1 Sukamaju to the ability to understand mathematical concepts of fifth grade students. This study used a Quasi-Experimental Research type. The results showed that the use of the AIR learning model could improve the ability to understand mathematical concepts of class V-A students at SD Negeri 1 Sukamaju in the 2022 academic year, this was demonstrated by an increase in the test results for understanding the ability of concepts from pretest to posttest. The average ability to understand mathematical concepts in the experimental class was 76.68, after being analyzed using the two average similarity test formula (t test) it showed that the value was > (2.4677 > -1.67722). In conclusion, H0 is rejected and Ha is accepted, so the hypothesis can be concluded that the average ability to understand mathematical concepts of elementary school students increases. Keywords: AIR learning model, understanding of mathematical concepts